2022
DOI: 10.1002/bse.3234
|View full text |Cite
|
Sign up to set email alerts
|

Green capabilities, green purchasing, and triple bottom line performance: Leading toward environmental sustainability

Abstract: Despite the vast literature on green purchasing practices and sustainability, the role of an organization's green capabilities in defining green purchasing practices for triple-bottom-line performance has received limited attention. This research intends to empirically evaluate the impact of green capabilities on green purchasing practices to boost the triple-bottom-line performance of manufacturing organizations. We analyzed 386 manufacturing organizations' responses using the covariance-based structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 107 publications
1
62
1
Order By: Relevance
“…Although other studies have found that green purchasing practices have a significant favorable association with environmental sustainability (Khan et al, 2022), our study does not show a robust positive relationship between the interaction of supplier integration and ECD and environmental performance (the relationship is marginally significant). It has been argued that integration with suppliers generates a constant flow of information that allows both parties to better understand whether the requirements necessary to keep working together have been met.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although other studies have found that green purchasing practices have a significant favorable association with environmental sustainability (Khan et al, 2022), our study does not show a robust positive relationship between the interaction of supplier integration and ECD and environmental performance (the relationship is marginally significant). It has been argued that integration with suppliers generates a constant flow of information that allows both parties to better understand whether the requirements necessary to keep working together have been met.…”
Section: Discussioncontrasting
confidence: 99%
“…Kong et al ., 2021; Samad et al ., 2021). However, there is a dearth of studies that jointly analyze the role of SCI and firm ECD (Khan et al ., 2022) and their complementary relationships. This is an important research question because it responds to the call to investigate how firms can enhance their environmental sustainability through the development of management practices supporting different strategic capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although GSCI provides enterprises with access to resources (Yang et al, 2020), it is still unclear how enterprises can use acquired resources to guide their green innovation practice in a competitive and dynamic market environment (Lyu et al, 2021;Khan et al, 2022b). Therefore, to fully understand the relationship between GSCI and firms' green innovation performance, the "black box" between their relationships should be opened.…”
Section: Introductionmentioning
confidence: 99%
“…Brand trust modifies a cumulative association with Instagram usage intensity (Bowden et al, 2018; C. T. Lee and Hsieh, 2016); members of C2C communities can influence other members and draw their attention to a specific brand. Instagram usage intensity reinforces the bond between members of C2C communities, thereby re-creating and modifying the linking value among consumers (Liu & Jiang, 2020;Khan et al, 2022e). Thus, we can postulate the below hypothesis: HYPOTHESIS 9.…”
Section: Social Capital and Brand Trustmentioning
confidence: 90%